Stigmatisasi terhadap individu childfree dalam komentar Youtube: analisis wacana kritis - Nashiroh, Tsalits Syafa'atun; Firmonasari, Aprillia (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This study aims to investigate the discourse of stigmatization of childfree individuals from Indonesian citizens’ perspective, represented in netizens’ comments on the childfree by choice of the Youtube account Menjadi Manusia. This study used a descriptive qualitative method with a critical discourse analysis approach from van Dijk’s perspective. The study conducted three stages of research: data collection, data analysis, and presentation of results. The data source was the comments column in the childfree by choice discussion video on the Menjadi Manusia Youtube account. Data in the form of written utterances were collected by reading and note-taking. The data were analyzed in aspects of discourse structure, speech strategies, and social cognition. The results elucidate the macro text structure is embodied in the theme. By this meaning, the utterances align with pro-childfree, neutral, and contra-childfree values. Contra-childfree utterance is more dominant rather than pro-childfree and neutral. Contra-childfree utterance uses several strategies: quoting religious text sources, using rhetorical questions, analogies, and argumentative language. Individuals who do not want a child are labeled with a negative stigma as they are considered against Indonesian society’s religion and sociocultural values. It indicates that the discourse tends to be dominated by pronatalist ideas that require women to have children.